A Correlation Study Between The Students’ Listening and Speaking Mastery of Vocational High School in Klaten - Widayanti, Sukasih Ratna; Anisa, Sahaya (IJET (Indonesian Journal of English Teaching), 2017)
This study aims to find out the correlation between the students’ listening and speaking mastery of Vocational High School in Klaten. There are two language skills correlated, such as listening and speaking. The sample is sixty two students in the tenth grade of State Vocational High School 1 Klaten. The writers calculate the correlation coefficient value by using the Pearson Product Moment formula. The rXY value is 0.352601. According to the r value on the r table, the level of significances of 5% and 1% for the sixty two students are 0.259 and 0.325. It can conclude that the rXY value is greater than the level of significances at 5% and 1% on the r table. Based on this result, the hypothesis in this study is accepted. It means that there is a significant correlation between the students’ listening and speaking mastery of Vocational High School in Klaten.